The confessions of Nat Turner - Styron, William, 1925-2006.; Kandinsky, Wolfram (Newport Beach, CA : Books on Tape, 1985)
Presents a fictionalized account of the 1831 slave revolt led by Nat Turner in Southampton County, Virginia.
An unabridged recording of the book read by Wolfram Kandinsky.
LC copy shows p1984 on cassettes 11-12.
Keywords: Turner, Nat, -- 1800?-1831 -- Fiction; Southampton Insurrection, 1831 -- Fiction; African American men -- Fiction; African Americans -- Fiction; Slaves -- Fiction; Virginia -- History -- 1775-1865 -- Fiction